2008
DOI: 10.1007/s00431-007-0661-2
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis in referred pediatric patients: demographic and clinical features, triggers, and therapeutic approach

Abstract: Anaphylaxis remains under-diagnosed and under-treated. A better knowledge of patterns and triggers of anaphylaxis might contribute to a better management. In this study we evaluated the demographic and clinical features of anaphylaxis in pediatric patients, as well as its triggers and therapeutic approach. From May 1st 2004 until April 30th 2006 we prospectively collected data on all patients referred for investigation of anaphylaxis to the pediatric department of the University Hospital Gasthuisberg Leuven an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
59
4
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 34 publications
17
59
4
7
Order By: Relevance
“…According to the anaphylaxis registries of different European countries, next to exercise, alcohol consumption is a relevant cofactor in up to 15.2% of anaphylactic events and drugs such as ASA were registered as a cofactor in 6.1-9% of severe anaphylactic reactions (Table 1). The role of infections as cofactors of anaphylaxis is reported to be relevant in 2.5-3% of anaphylactic reactions in children and in 1.3-11% in adults (8,(13)(14)(15)(16)(17)(18). Infections are particularly dangerous for patients with a risk to develop anaphylaxis, because in contrast to most other relevant cofactors of anaphylaxis, infections cannot simply be avoided or foreseen.…”
mentioning
confidence: 99%
“…According to the anaphylaxis registries of different European countries, next to exercise, alcohol consumption is a relevant cofactor in up to 15.2% of anaphylactic events and drugs such as ASA were registered as a cofactor in 6.1-9% of severe anaphylactic reactions (Table 1). The role of infections as cofactors of anaphylaxis is reported to be relevant in 2.5-3% of anaphylactic reactions in children and in 1.3-11% in adults (8,(13)(14)(15)(16)(17)(18). Infections are particularly dangerous for patients with a risk to develop anaphylaxis, because in contrast to most other relevant cofactors of anaphylaxis, infections cannot simply be avoided or foreseen.…”
mentioning
confidence: 99%
“…5,7,12,13 Novembre et al 13 found out male predominance of 2:1 and hypothesized that it might be attributable to the larger number of boys with hymenoptera sting or exercise-induced anaphylaxis. In our study, male predominancy was obvious in venom induced anaphylaxis (68%) and in children £ 2 years old (74%).…”
Section: Discussionmentioning
confidence: 97%
“…In our study, drugs mainly antibiotics and nonsteroid anti-inflammatory medications took the first place in the etiology of anaphylaxis rather than food which was determined as the first offending agent in other studies, [5][6][7]12 . In a study carried out by Dibs and Baker 14 , food was the second trigger after latex.…”
Section: Discussionmentioning
confidence: 98%
“…The major triggers of anaphylaxis in adults are drugs, food, and venom [11••, 12, 27], respectively, whereas in children the major triggers are food, drugs, venom, and unknown causes (Table 2) [2,3,15,17,18,20,21,29]; interestingly, galactose-α-1,3 galactose sensitivity, and delayed anaphylaxis recently documented in children has not be reported in children with mastocytosis [30].…”
Section: Introductionmentioning
confidence: 99%